PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN DISIPLIN KERJA SEBAGAI VARIABEL MODERASI DI DINAS PEREHUBUNGAN KABUPATEN MUSI RAWAS - Surajiyo, Surajiyo; Idayati, Irma; Aziz, Hairul (LPPM UNIVERSITAS BINA INSAN, 2021)
This study entitled The Effect of Motivation on Employee Performance with Work Discipline as a Moderation Variable in the Transportation Office of Musi Rawas Regency. with respondents as many as 40 people.”This study aims to determine the effect of motivation on employee performance with work discipline as a moderating variable. The method used in this research is quantitative methods and data collection techniques used in this research are using observations, interviews, questionnaires and documentation. The data analysis technique used is simple regression test, correlation coefficient, t test, and moderation test. Testing the first hypothesis, namely the variable Motivation (X1) on Employee Performance (Y) shows that tcount produces a coefficient of 5000. With a sample size of 40, it is found that df = (40-2) and at a significance level of 0.05, the t table value is 1.686. With these results it can be said that motivation (X1) has a significant effect on Pegwai's performance because tcount (5000)> ttable (1.686). Then the second hypothesis testing shows that there is an increase in the R square value from 0.397 to 0.533.”This means that the Work Discipline variable (X2) can strengthen the relationship between Motivation (X1) and Employee Performance (Y). So with this variable Work Discipline (X2) is Pemoderation in the relationship between Motivation (X1) and Employee Performance (Y).